Estimating a unit price for roads maintenance activities using exponential robust regression - Moena, Cristóbal; Serpell, Alfredo (Journal of Civil Engineering and Management, 2014)
Good road maintenance schemes allow reducing costs and extending the service life of roads. There are several methods to plan these project maintenances but all of them require input information about maintenance costs, which can be very different depending on the geographical zone and the contracted volume. Nowadays agencies do not have written documentation on the entire process for preparing project estimates, and experience plays an important role in price estimation. In this paper, a structured methodology for estimating a unit price for road maintenance activities is proposed, modeling the exponential decay nature of economies of scale. Using an exponential robust regression procedure, curves are adjusted and parameters generated. Additionally, a cost contingency analysis is performed in order to provide cost ranges associated to specific contracted volumes. The validation of the methodology was carried out through its use in the estimation of real unit prices of historic road maintenance projects in Chile. The procedure may be used by road planners as well ascontractors looking for a more confident approach before participating in a bid. Furthermore, this methodology is not limited to road maintenance only, but also to any other field where economies of scale and exponential fitting are needed.